Two new records of the orthotyline plant bug (Hemiptera: Heteroptera: Miridae) from the Korean Peninsula - Junggon Kim (Journal of Asia-Pacific Biodiversity, 2017)
Two new records of the subfamily Orthotylinae (Heteroptera: Miridae: Orthotylinae), Zanchius tarasovi Kerzhner, 1988 and Orthotylus bilineatus (Fallén, 1807), are reported for the first time to the Korean fauna. The genus Zanchius is also first recorded from the Korean Peninsula. Redescriptions of genitalia, diagnoses of each species and genus, and biological notes are presented with the photographs and illustrations.